Crystalline olefin-linked chiral covalent organic frameworks as a platform for asymmetric catalysis - He, Ting (2024)
The construction of olefin-linked chiral covalent organic frameworks (COFs) with high crystallinity is highly desirable while remains great challenge due to the poor reversibility of the formation reaction for the olefin linkages during the in situ structural self-healing process. Herein, we successfully synthesized two sets of enantiomeric olefin-linked COFs. The chiral catalytic groups are uniformly distributed on the pore walls of COFs, resulting in the full exposure of catalytic sites to the reactants in asymmetric catalysis. The as-prepared (R)/(S)-CCOF8 exhibits excellent catalytic performance with exceeding 99 % enantiomeric excess in the enantioselective electrophilic amination reaction. Moreover, the heterogeneous chiral catalysts are conveniently recycled and could maintain the performance after ten catalytic cycles. Our findings expand the scope to construct stable and crystalline chiral COFs for the asymmetric catalysis.